Analysis of a 4-legged fixed offshore structure in Malaysia under seismic loading - Low,, Yee Hwa (2015)
Most structures in Malaysia do not consider for seismic design during its service lifetime. However, structures in Malaysia might be affected by the tremors of earthquake from neighbouring countries such as Philippines, Indonesia etc. The aim of this study is to identify the necessity of implementation of seismic design in offshore structures due to earthquake loading. Thus, this research presents a finite element simulation of a 4-legged offshore structure using SAP2000. The structure is in three dimensional form and it is tested with dead load, live load and environmental load such as wind, wave and current load with addition of earthquake ground accelerations from Aceh earthquake. The response of the structure due to the above loading's are illustrated and discussed. Results such as the natural frequencies, vibration modes of the structure, displacement, bending moment and shear stress, interaction ratio of members etc. are collected and analyzed. Generally, the offshore structure with consideration of seismic ground motion is still within members capacity desirable range. In summary, the fourlegged fixed offshore structure is yet consider safe and does not require seismic design for this moment of time.